Guide to financial markets - Levinson, Marc. ([S.l.] : Profile Books, 2002)
Financial markets play a hugely important role in the modern economy and globalisation of them markets continues apace. Electronic trading has led to exponential year by year growth in trading on the money and foreign exchange markets. And billions of dollars-worth of derivatives in all kinds of new and fancy - and often almost incomprehensible - forms are created and sold daily. Stock markets have bubbled and burst, proving that their performance can never be taken for granted and giving the bond market a fillip. This book provides a brilliantly clear guide to this complex world that even those who work in it often find hard to understand. With chapters on the markets that deal in money, foreign exchange, equities, bonds, commodities, financial futures, options and other derivatives, it looks at why these markets exist, how they work and who trades in them, and it gives a run-down of the factors that affect prices and rates.